Application of Histone Deacetylase Inhibitors in Renal Interstitial Fibrosis - Nie, Ling (Kidney Dis (Basel), 2020)
BACKGROUND: Renal interstitial fibrosis is characterized by the accumulation of extracellular matrix proteins, which is a common feature of chronic kidney diseases. SUMMARY: Increasing evidence has shown the aberrant expression of histone deacetylases (HDACs) in the development and progression of renal fibrosis, suggesting the possibility of utilizing HDAC inhibitor (HDACi) as therapeutics for renal fibrosis. Recent studies have successfully demonstrated the antifibrotic effects of HDACis in various animal models, which are associated with multiple signaling pathways including TGF-β signaling, EGRF signaling, signal transducer and activator of transcription 3 pathway, and JNK/Notch2 signaling. This review will focus on the utilization of HDACi as antifibrotic agents and its relative molecular mechanisms. KEY MESSAGES: HDACis have shown promising results in antifibrotic therapy, and it is rational to anticipate that HDACis will improve clinical outcomes of renal fibrosis in the future.